Culturally Responsive Leadership: A Framework to Merge Eastern and Western Educational Philosophies in an Era of Increasing Globalization - Antik K. Dey (Canadian Society for Studies in Education, 2022)
In the era of increasing globalization, education has become one of the media through which political, economic and cultural ideas are exchanged between nations and people. This paper looks at the dynamics and the epistemological challenges of delivering a Western (Canadian) curriculum, from the Deweyan lens, in an East Asian schooling context, namely China, that predominantly views education through the Confucian lens. I will employ a self-study research methodology to highlight some of these challenges, and demonstrate how the four pillars of the Culturally Responsive Leadership (CRL) framework can enhance cultural exchange and close the epistemological gap in a high school setting. This study underscores the importance of hiring and training culturally humble educators. Looking ahead, it will be beneficial to develop more strategies on ways teachers and leaders can unpack their biases when implementing the CRL framework; and develop an appreciation for other epistemological lenses through which one can narrow the gap between Eastern and Western educational philosophies. This way, educators can continue to promote cross-cultural understanding, which can potentially move us towards a more caring and inclusive world. Key words: globalization, epistemological gap, culturally responsive leadership, culturally humble educator, cross-cultural understanding, inclusive world